Women and female entrepreneurship: Past, present, and future trends in developing countries - Muhammad Ashraf, Fauzi; Noraina Mazuin, Sapuan; Nurhaizan, Mohd Zainudin (University of Cracow, Poland, 2023)
Objective: This article provides an understanding of the knowledge structure based on the publications on women’s entrepreneurship in developing and emerging countries based on bibliometric analysis. Women entrepreneurs play a pivotal role in economic and social development. Research Design & Methods: By analysing citations, co-citations, and co-words, this study unveiled the most significant publications in the study context, link their knowledge structure, and map future research direction based on the two analyses, respectively. From the Web of Science (WoS), 208 journal publications were obtained. Findings: Four themes were discovered in the co-citation analysis: 1) differences between men and women entrepreneurs, 2) the development of women’s entrepreneurship, 3) challenges among women entrepreneurs in developing countries, and 4) progress in women’s entrepreneurship studies. Subsequently, four themes were discovered in the co-word analysis: 1) innovation in women’s entrepreneurship, 2) women’s entrepreneurship performance, 3) empowerment of women entrepreneurs, and 4) self-employment and assistance to women entrepreneurs. Implications & Recommendations: Theoretical and practical implications are presented by enhancing and developing women’s entrepreneurship participation in developing countries. Contribution & Value Added: This review provides a comprehensive knowledge structure based on the past, present, and future trends in women’s entrepreneurship in developing countries.